Experimental Models, Induction Protocols, and Measured Parameters in Dry Eye Disease: Focusing on Practical Implications for Experimental Research - Md. Mahbubur Rahman (MDPI AG, 2021)
Dry eye disease (DED) is one of the major ophthalmological healthcare challenges worldwide. DED is a multifactorial disease characterized by a loss of homeostasis of the tear film, and its main pathogenesis is chronic ocular surface inflammation related with various cellular and molecular signaling cascades. The animal model is a reliable and effective tool for understanding the various pathological mechanisms and molecular cascades in DED. Considerable experimental research has focused on developing new strategies for the prevention and treatment of DED. Several experimental models of DED have been developed, and different animal species such as rats, mice, rabbits, dogs, and primates have been used for these models. Although the basic mechanisms of DED in animals are nearly identical to those in humans, proper knowledge about the induction of animal models is necessary to obtain better and more reliable results. Various experimental models (in vitro and in vivo DED models) were briefly discussed in this review, along with pathologic features, analytical approaches, and common measurements, which will help investigators to use the appropriate cell lines, animal, methods, and evaluation parameters depending on their study design.